Monitoring and Assessment Techniques for Microplastics - Chenhao, Zhou; Zhonghao, Chen; Mahmoud, Nasr; Ahmed I., Osman; Lai, Zhi Ying; Yiin, Chung Loong; Bridgid Chin, Lai Fui; Yap, Pow Seng (Springer Nature Switzerland AG, 2024)
The pervasive presence of microplastics in the environment has raised significant concerns regarding their impact on ecosystems and human health. This chapter begins by introducing the concept of microplastics, emphasizing their role as emerging pollutants and their detrimental effects on the environment. The core of this chapter focuses on the practical aspects of monitoring microplastics. It covers sampling and collection techniques, discussing considerations for different environmental matrices such as water, sediments, soils, and biological tissues. Furthermore, it investigates the various analytical methods, encompassing microscopy-based techniques, spectroscopy, and chemical methods. A thorough discussion of the strengths and limitations of these methods is provided, enabling readers to make informed choices for their specific monitoring needs. Data analysis and interpretation are crucial for drawing meaningful conclusions from monitoring efforts, and this chapter provides insights into best practices in data processing. It addresses the importance of data quality, statistical methods, and data visualization in understanding the extent of microplastic contamination. In addition, it offers a compilation of real-world case studies showcasing the application of monitoring and assessment techniques in diverse environmental settings, illustrating the relevance of these techniques in addressing the challenges of microplastic contamination. The chapter concludes by addressing current challenges and limitations in microplastic monitoring, presenting emerging trends and innovations in the field, and suggesting future research directions. Overall, this chapter underscores the paramount significance of monitoring and assessment techniques in understanding and mitigating the effects of microplastics on our environment, thereby contributing to a more sustainable and less polluted future.